2021
DOI: 10.1016/j.ijpp.2021.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Fancy shoes and painful feet: Hallux valgus and fracture risk in medieval Cambridge, England

Abstract: Objective Hallux valgus, the lateral deviation of the great toe, can result in poor balance, impaired mobility and is an independent risk factor for falls. This research aims to compare the prevalence of hallux valgus in subpopulations of medieval Cambridge, England, and to examine the relationship between hallux valgus and fractures to examine the impact of impaired mobility and poor balance caused by this condition. Materials 177 adult individuals from four cemeteries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…A study of different groups of people living in and around Cambridge during this period showed that 10%-45% of those living in the town had hallux valgus, compared with just 3% of those who lived in a rural farming community outside Cambridge. It was also found that fractures were significantly more common in those with hallux valgus than those without, which matches what we know about the increased risk of falls (Dittmar et al, 2021). This highlights how human behavior associated with urbanization, mediated by variation in income between rural and urban areas and coupled with access to the latest fashions, can lead to adverse health consequences in the past.…”
Section: Paleopathology and Urbanizationsupporting
confidence: 74%
“…A study of different groups of people living in and around Cambridge during this period showed that 10%-45% of those living in the town had hallux valgus, compared with just 3% of those who lived in a rural farming community outside Cambridge. It was also found that fractures were significantly more common in those with hallux valgus than those without, which matches what we know about the increased risk of falls (Dittmar et al, 2021). This highlights how human behavior associated with urbanization, mediated by variation in income between rural and urban areas and coupled with access to the latest fashions, can lead to adverse health consequences in the past.…”
Section: Paleopathology and Urbanizationsupporting
confidence: 74%
“…1). A total of 44 papers [9–52] were included ( n= 186,262,669). These epidemiological studies came from five continents and 17 different national regions (Table 1).…”
Section: Resultsmentioning
confidence: 99%